2013
DOI: 10.1016/j.freeradbiomed.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin D deficiency in rats from middle to old age leads to elevated tyrosine nitration and proteomics changes in levels of key proteins in brain: Implications for low vitamin D-dependent age-related cognitive decline

Abstract: In addition to the well-known effects of vitamin D (VitD) in maintaining bone health, there is increasing appreciation that this vitamin may serve important roles in other organs and tissues, including the brain. Given that VitD deficiency is especially widespread among the elderly, it is important to understand how the range of serum VitD levels that mimic those found in humans (from low to high) affects the brain during aging from middle-age to old-age. To address this issue, twenty-seven male F344 rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 115 publications
2
37
0
2
Order By: Relevance
“…In this instance, it was suggested that vitamin D may promote rather than suppress L. major infection. Conversely, rats on a low-vitamin D diet showed a global elevation of 3-nitrotyrosine in comparison to control and highvitamin D-treated animals, suggesting an increase nitrosative stress in the vitamin D-deficient brain (54).…”
Section: Discussionmentioning
confidence: 86%
“…In this instance, it was suggested that vitamin D may promote rather than suppress L. major infection. Conversely, rats on a low-vitamin D diet showed a global elevation of 3-nitrotyrosine in comparison to control and highvitamin D-treated animals, suggesting an increase nitrosative stress in the vitamin D-deficient brain (54).…”
Section: Discussionmentioning
confidence: 86%
“…Oxidative/nitrosative stress associated with increased generation of reactive oxygen and nitrogen species as well as impaired effectiveness of antioxidant defense has recently been recognized as one of the key mechanisms in the pathogenesis of various disorders associated with 25OHD 3 deficiency [10]. To clarify whether alterations of oxidative metabolism are involved in the development of cellular Fig.…”
Section: Resultsmentioning
confidence: 99%
“…*P = 0.01; **P = 0.001. Reported in Table 1 of Keeney et al (35). responsiveness with high VitD3 did not appear to be due to hyperexcitability, because slice survival and integrity were comparable across groups.…”
Section: Significancementioning
confidence: 86%